Qur'anic governance : family vs state - Kamaruddin, Zaleha (2010)
Good governance is considered a crucial element for peace and development of societies because it implies good order and good policies. In the context of family institution, this is a must so as to ensure that the basic unit of society is protected from destruction. In relation to this, most scholars have acknowledge that all over the world, the family has undergone radical transformations in response to the changing socio-economic environment, however the breadth and depth of this changes in the realm of good governance has never been explored in grater detail. It is in this context that this project is taken up.